Examining the role of trauma in alcohol interlock performance: A structural pathway analysis. (29th March 2022) - Scherer, Michael; Nochajski, Thomas H.; Romano, Eduardo; Romosz, Ann; Evans, Kierra; Taylor, Eileen; Voas, Robert
Abstract: Objective: Self-medication using alcohol is a common coping response among individuals dealing with trauma as is driving under the influence of alcohol (DUI). A common intervention for drivers convicted of DUI, is an alcohol ignition interlock device (IID)—which requires breath samples before starting the car. If the sample is above a predetermined limit (.025), the car will not start, thus preventing impaired driving. IIDs are an effective intervention to reduce rates of drinking and driving among high risk populations; however, limited research has examined how traumatic experiences may impact performance on IIDs. Methods: This study is an archival analysis of the Managing Heavy Drinking (MHD) study of drivers in New York state. The MHD is a comprehensive study of drivers convicted of a DUI from 2015–2020. Participants (N = 121) completed questionnaires and provided consent to retrieve information from interlock providers. Outcome variable included high BAC lockout ratios (number of high BAC lockouts [BAC>.08]/number of clean blows [BAC ≤ .025]). Other variables included demographic variables, alcohol treatment history, trauma experiences, and prior DUI history. Variables were entered into a structural equation model. Results: In the final structural model, pathways that demonstrated a p -value of greater than .10 were dropped from the model. This produced acceptable overall model fit statistics (χ2 = 27.059(10), p =.003; CFI = .900; NFI = .898; RMSEA = .063). A significant pathway was found from the trauma measure to alcohol use ( β = .132), and from alcohol use to interlock performance ( β = .636). However, no significant relationship was found between trauma and interlock performance other than through alcohol use. Conclusions: The current study provides a useful framework upon which to understand the role traumatic experiences have on alcohol IID performance. Traumatic experiences are in of themselves insufficient to impact IID performance directly, but it may indirectly impact IID performance through increasing alcohol use.